Evaluation of the Cause of Dental Treatment in Children under General Anesthesia from the Perspective of Pediatric Dentists and Postgraduate Students and Parents of Children under General Anesthesia at the Dentistry School of Tehran University of Medical Science - Alireza Heidari; Mehdi Shahrabi; Zohre Salehi; Fateme Kalantari; Zahra Salehi (International Journal of Dentistry)
Background. Nowadays, dental treatment under general anesthesia is accepted as a treatment method in children in which other common methods do not allow to achieve acceptable results. The benefits of general anesthesia in pediatric dental treatment are that the treatment is completed in one session, the person is relieved of pain, and most importantly, the child does not need to cooperate. However, it is important to determine the exact dental reasons for children under general anesthesia. Objective. In this study, the cause of dental treatment under general anesthesia in children was examined from the perspective of specialists, assistants, and parents of children under general anesthesia. Methods. In this descriptive-analytical cross-sectional study, participants were selected from among the parents of children under general anesthesia for dental treatment and pediatric dentists and assistants in a purposeful manner. After the items were prepared by the professors, the prepared checklist was read to the people. After completing the checklist, the data were entered into SPSS software version 20 and analyzed using descriptive statistics such as frequency determination, mean, and statistical rests. Results. According to the consensus of parents and experts, the main reasons for general anesthesia for children to perform their dental operations were: young age, lack of cooperation during previous dental treatment, a large number of dental treatments, systemic disease of the child, unwillingness of parents to perform behavioral control procedures, higher quality work under anesthesia, mental and physical behavioral problems, and reduced number of treatment sessions. Conclusion. Therefore, reasons such as young age, lack of cooperation, and a large number of dentist’s work are among the most important factors that lead to the decision to perform general anesthesia in children. In light of this decision, the consequences and disadvantages/advantages of this method are important and therefore more research should be done on this issue.